Factors affecting applied perception and applicability of fair value accounting: The case of construction firms in Vietnam - Tung Nguyen Thanh; Hai Phan Thanh; Nhan Ho Van; Tien-Thuy Thi Vo; Mai Thi Thuong (Problems and Perspectives in Management, 2023)
This study determines and measures the factors affecting the perception and applicability of fair value accounting by related personnel in enterprises, including business owners, managers, accountants, and internal auditors. At the same time, it analyzes the relationship between applied perception and the applicability of fair value accounting. 808 respondents, working in 350 construction enterprises in Vietnam, participated in the survey. This study combines qualitative and quantitative methods using SPSS and AMOS 20 with different techniques and structural equation modeling. The study results show that the applied perception significantly affects the applicability of fair value accounting at construction enterprises in Vietnam. Besides, eight different factors influence the applied perception of fair value accounting. Notably, six factors positively influenced the applied perception, including usefulness, reliability, cost-benefit relationship, size of the enterprise, qualification of accountants, and independent auditors. In contrast, two factors, legal matters and tax pressure, negatively affected the applied perception. This study suggests that managers of Vietnam’s construction enterprises develop solutions to improve the applied perception and applicability of fair value accounting, thereby perfecting the system accounting and improving business performance. AcknowledgmentThis study is conducted within the framework of the doctoral project subject to Decision No. 1407/QD-ĐHDT dated May 22, 2020, Duy Tan University, Vietnam. The authors would like to acknowledge the reviewers and the editor-in-chief for their assistance.